Impact Of Parental Phubbing on Smartphone Usage, Relationship Assessment and Emotional Intelligence - Hafsa Awan; Prof Aneeza Bashir (Social Science Review Archives, 2025)
The present study examined the impact of parental phubbing on smartphone usage, emotional intelligence and relationship assessments among students (N=302) from Sargodha. The study follows correlational research design Students were selected by using purposive convenient sampling technique. In order to measure parental phubbing, smartphone usage, emotional intelligence and relationship assessments parental phubbing Questionnaire (Roberts and David 2016) smartphone usage Questionnaire (Kwon et al. 2013), emotional intelligence Questionnaire (Law, Wong, & Song, 2004) and relation assessment scale (Hendrick, 1988) has been used. Psychometric properties and descriptive were determined to ensure the normality of sample. Correlation analysis depicted Parental phubbing is positively corelated with smartphone usage and negatively corelated with relationship assessment.